1986
DOI: 10.1126/science.2422758
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Hormone Metabolites Are Barbiturate-Like Modulators of the GABA Receptor

Abstract: Two metabolites of the steroid hormones progesterone and deoxycorticosterone, 3 alpha-hydroxy-5 alpha-dihydroprogesterone and 3 alpha, 5 alpha-tetrahydrodeoxycorticosterone, are potent barbiturate-like ligands of the gamma-aminobutyric acid (GABA) receptor-chloride ion channel complex. At concentrations between 10(-7) and 10(-5)M both steroids inhibited binding of the convulsant t-butylbicyclophosphorothionate to the GABA-receptor complex and increased the binding of the benzodiazepine flunitrazepam; they also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
950
0
24

Year Published

1988
1988
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,091 publications
(1,023 citation statements)
references
References 38 publications
27
950
0
24
Order By: Relevance
“…We have shown that clozapine, but not haloperidol or sulpiride, increases in a dose-and time-dependent manner the brain concentrations of progesterone as well as AP and THDOC, two potent endogenous positive modulators of the action of GABA at GABA A receptors (Majewska et al 1986;Robel and Baulieu 1994;Gee et al 1995;Lambert et al 1995), to an extent compatible with modulation of GABA A receptor activity in vivo (Pinna et al 2000). The active doses of clozapine with regard to this effect, as well as the doses of haloperidol used in this study, are comparable to those that are therapeutically efficacious in humans.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We have shown that clozapine, but not haloperidol or sulpiride, increases in a dose-and time-dependent manner the brain concentrations of progesterone as well as AP and THDOC, two potent endogenous positive modulators of the action of GABA at GABA A receptors (Majewska et al 1986;Robel and Baulieu 1994;Gee et al 1995;Lambert et al 1995), to an extent compatible with modulation of GABA A receptor activity in vivo (Pinna et al 2000). The active doses of clozapine with regard to this effect, as well as the doses of haloperidol used in this study, are comparable to those that are therapeutically efficacious in humans.…”
Section: Discussionmentioning
confidence: 95%
“…Allopregnanolone (AP) and allotetrahydrodeoxycorticosterone (THDOC) are endogenous neuroactive steroids that potentiate the action of GABA at GABA A receptors with high potency both in vitro (Majewska et al 1986;Puia et al 1990;Paul and Purdy 1992;Lambert et al 1995) and in vivo (Concas et al 1996;Pinna et al 2000). The brain concentrations of AP and THDOC are increased by convulsant and anxiogenic drugs, such as isoniazid and negative allosteric modulators of GABA A receptors (Barbaccia et al 1996b(Barbaccia et al , 1997, that reduce GABA-mediated transmission; this action is possibly mediated through a decrease in the GABAergic inhibition of the hypothalamic-pituitaryadrenal axis.…”
mentioning
confidence: 99%
“…[11][12][13] This neurosteroid potentiates the inhibitory actions of g-aminobutyric acid (GABA) by modulation of the GABA A receptor. 14 Consistent with this GABAergic mechanism, progesterone and allopregnanolone administration usually produce an anxiolytic effect 11,13 by the action on the amygdala. 15 Also pregnanolone, the less potent 5b stereoisomer of allopregnanolone that has a similar effect, 16,17 can produce anxiolysis.…”
Section: Introductionmentioning
confidence: 94%
“…In the case of corticosterone, rapid effects have been identified in amphibians on various measures of sexual behavior (Moore and Orchinik, 1994) and stress (Orchinik, 1998) and there is good evidence for a highly specific membrane-binding site (Evans, Searcy, and Moore, 2000;Orchinik, Murray, and Moore, 1991). For progesterone, several lines of evidence indicate rapid, membrane effects on sexual behavior in the ventral tegmental area of Syrian hamsters (DeBold and Frye, 1994;Frye and Petralia, 2003) and this steroid or its metabolites can clearly bind to membrane receptors such as the GABA-A complex (Majewska, Harrison, Schwartz, Barker, and Paul, 1986;Zhu, Bond, and Thomas, 2003;Zhu, Rice, Pang, Pace, and Thomas, 2003). In one study, testosterone was similarly shown to exert rapid effects on striated penile muscles related to the expression of male sexual behavior (Sachs and Leipheimer, 1988).…”
Section: Introductionmentioning
confidence: 99%